Cardiopulmonary-induced deformations of the thoracic aorta following thoracic endovascular aortic repair. (April 2019) - Suh, Ga-Young; Ullery, Brant W.; Lee, Jason T.; Dake, Michael D.; Fleischmann, Dominik; Cheng, Christopher
Objectives: Thoracic endovascular aortic repair has become a preferred treatment strategy for thoracic aortic aneurysms and dissections. Yet, it is not well understood if the performance of endografts is affected by physiologic strain due to cyclic aortic motion during cardiac pulsation and respiration. We aim to quantify cardiac- and respiratory-induced changes of the postthoracic endovascular aortic repair thoracic aorta and endograft geometries. Methods: Fifteen thoracic endovascular aortic repair patients (66 ± 10 years) underwent cardiac-resolved computed tomography angiographies during inspiratory/expiratory breath holds. The computed tomography angiography images were utilized to build models of the aorta, and lumen centerlines and cross-sections were extracted. Arclength and curvature were computed from the lumen centerline. Effective diameter was computed from cross-sections of the thoracic aorta. Deformation was computed from the mid-diastole to end-systole (cardiac deformation) and expiration to inspiration (respiratory deformation). Results: Cardiac pulsation induced significant changes in arclength, mean curvature, maximum curvature change, and effective diameter of the ascending aorta, as well as effective diameter of the stented aortic segment. Respiration, however, induced significant change in mean curvature and effective diameter of the ascending aorta only. Cardiac-induced arclength change of the ascending aorta was significantly greater than respiratory-induced arclength change. Conclusions: Deformations are present across the thoracic aorta due to cardiopulmonary influences after thoracic endovascular aortic repair. The geometric deformations are greatest in the ascending aorta and decline at the stented thoracic aorta. Additional investigation is warranted to correlate aortic deformation to endograft performance.